Nanostructured colloidal crystals from forced hydrolysis methods - Otal, Eugenio Hernan (2009)
In this work, an original route for ZnO nanostructured spherical colloids and their assembly into colloidal crystals are presented. The temporal evolution of crystal size and shape was followed by X-ray diffraction and the colloids size distribution by scanning electron microscopy. These spherical colloids showed a change in their size dispersion with aging time. Early stage suspensions, with a narrow size distribution, were settled to the bottom and dried with a slow evaporation rate to obtain colloidal crystals. This original route provides a new material for future applications in opalline photonic crystals, with a dielectric constant higher than that of classical materials (silica and latex). Moreover, this route means an improvement of previously reported data from the literature since it involves a one-pot strategy and room-temperature colloid assembly.